Top-K Spatial Preference Query with Range Based Skyline Query in Mobile Environment - Steffi, R. Prema; Sundaramoorthy, S (International Journal of Computer Sciences and Engineering, 2014)
As the location based service makes the users to process their queries from anywhere and at anytime, the spatial query processing that with this provides the processing on the basics of the spatial attributes in the skyline. With thus provides the users to identify the nearest neighbour among their query given with its spatial attributes. With the existing, they have done the skyline query processing based on the range in the spatial attribute for analyzing the nearest among the other skyline data sets. They have done these using two novel algorithms as index and non index algorithm. We are going to concentrate by making with that range query to process on the basis of userï¿½s feedback as their rating for the skyline query processing. Here the processing is done by ranking on the spatial attribute in the skyline data sets. When the user makes the feedback as their rating for the result of the skyline, this will be also analyzed while considering the next query processing for the nearest neighbour in the skyline query processing. Here, we are going to consider the algorithms as nearest neighbour algorithm and branch and bound algorithm in which this makes the analysis on the basics of both nearest and the minimum bound within the skyline.